Effect of Xuezhikang Therapy on Expression of Pulmonary Hypertension Related miR-638 in Patients With Low HDL-C Levels - Cao, Ruihua; Sun, Tao; Xu, Ruyi; Zheng, Jin; Wang, Hao; Wang, Xiaona; Bai, Yongyi; Ye, Ping (Frontiers in Pharmacology, 2021)
Objective: Down-regulation of miR-638 have been proved to be associated with pulmonary hypertension. Low plasma level of high-density lipoprotein cholesterol (HDL-C) associated with poor outcomes in several cardiovascular diseases, including pulmonary arterial hypertension. The main aim of this study was to evaluate the expression and specific role of miR-638 after lipid-lowering therapy in patients with low (HDL-C). Methods: In 3 subjects with low HDL-C and 3 subjects with normal HDL-C, we found 20 microRNAs had significant difference by chip screening. In 20 subjects with low HDL-C and 20 subjects with normal HDL-C, we found miR-638 had significant difference. Finally, we identified miR-638 as the research targets. A total of 40 subjects with low HDL-C were assigned to receive an XZK therapy for 6 months, we analyzed the relationship between plasma miR-638 expression and HDL-C levels. Results: In 20 subjects with low HDL-C and 20 subjects with normal HDL-C, the miR-638 expression were higher in normal HDL-C group (P<0.05). In the study of Xuezhikang treatment, HDL-C was divided into group A (HDL-C < 1.1mmol/L) and group B (HDL-C ≥ 1.1mmol/L) according to the median of baseline HDL-C level. After Xuezhikang treatment, the mean HDL-C level was 1.19 mmol/L, presenting an increase of 11.2% from baseline (P<0.001). The miR-638 expression was increased from baseline (P<0.05), especially in group A (P<0.01). The changes of miR-638 were inversely associated with baseline HDL-C levels. Conversely, the changes of miR-638 was positively correlated with the baseline triglyceride (TG) levels. Multivariate logistic regression analysis demonstrated that the changes of miR-638 was independently related to lower HDL-C levels. Conclusions: In patients with low HDL-C levels, XZK therapy raised the expression of miR-638, suggesting that XZK may have potential value in the treatment of pulmonary hypertension by regulating HDL-C metabolism and miR-638 expression.